COMPARATIVE ANALYSIS OF RICE FARMER INCOME USING AND NOT USING COMBINE HARVESTER HARVESTER TOOLS IN PADANG VILLAGE, MANGGENG DISTRICT, ACEH BARAT DAYA DISTRICT - Asmaul Husna; Devi Agustia (RADJA PUBLIKA, 2023)
This research aims to analyze the comparison of the income of rice farmers who use combine harvesters and farmers who do not use combine harvesters in Padang Village, Manggeng District, Southwest Aceh Regency. The methods used are observation data collection techniques, direct interviews using questionnaires while data analysis uses quantitative descriptive methods. 95% test (0.05) comparative testing of the income of rice farmers who do not use combine machines and the income of rice farmers who use combine machines, shows a significant difference between the test values, where the t test shows that tcount = 5.70. Meanwhile ttable is 1.666. Because tcount > ttable, namely 5.70 > 1.666, it means that Ho is rejected and Hi is accepted, so it can be concluded that farmers' income with the use of combine machines will cause an increase in income. Thus, the difference between the income of rice farmers who do not use combine machines and the income of rice farmers who use combine machines at the 0.05 level, namely 0.000 < 0.05, is significantly different and causes an increase in income in Padang village, Manggeng District, Aceh Barat Daya Regency.